Studies on Anomalous Behaviour at Curie Point Tc of Some Classes of Mixed Ferrites (Bangladesh Journal of Scientific and Industrial Research, 2007)
A comparative studies on anomalous behaviour at Curie point between clay additives Mn-Zn ferrites and other mixed ferrites such as Mn-Zn, Ni-Zn, Mg-Mn and Ni-Mg have been carried out in this investigation. The changes in Tc on compositions, additives and manufacturing processes of such soft mixed ferrites have been determined from the temperature dependent dc resistivity data and the log ρ vs. (1/1000T) graphs. It is observed that the Curie temperature is dependent on compositions, additives, manufacturing process and microstructure. Definite changes of Curie points of clay additives Mn-Zn ferrites with other ferrites were observed. Both the Mn-Zn ferrites and clay additives Mn-Zn ferrites showed some changes in their T sub>c behavior. The T sub>c value of Mn-Zn ferrites with clay additives decreases with increasing additives. In the case of clay substituted Mn-Zn ferrites the decrease of Curie point can be understood by a decrease of the number of Fe3+ magnetic ions substituted by nonmagnetic Al3+ ions on O sites of the system.Bangladesh J. Sci. Ind. Res. 41(3-4), 171-180, 2006